2012 IEEE 11th International Conference on Trust, Security and Privacy in Computing and Communications 2012
DOI: 10.1109/trustcom.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Fast Symmetric Cryptographic Algorithm Based on the Chaos Theory for Wireless Sensor Networks

Abstract: Wireless sensor networks are being more and more considered for critical applications where security issues are a priority. Security protocols are based on complicated algorithms that are very time consuming. The limited processing capabilities of sensor nodes make these protocols even more time consuming. Security algorithms based on the theory of chaos have been introduced in order to reduce the complexity of cryptographic operations. A novel chaos based algorithm aiming at enhancing the security robustness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The chaos maps are often based on the floating-point computations [16], [38], which demand greater precision and energy, hence inappropriate for systems with resource constraints such as wireless networks. In some of the proposed methods, chaos maps along with the floating-point computations are also used prior to the encryption process, e.g., key generation process [39].…”
Section: B Chaos-based Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chaos maps are often based on the floating-point computations [16], [38], which demand greater precision and energy, hence inappropriate for systems with resource constraints such as wireless networks. In some of the proposed methods, chaos maps along with the floating-point computations are also used prior to the encryption process, e.g., key generation process [39].…”
Section: B Chaos-based Solutionsmentioning
confidence: 99%
“…Table 3 shows the characteristics of a number of chaosbased encryption algorithms in wireless sensors that are compared in two dimensions of performance and security. The article [38] and [39] were implemented and [7], [14], and [16] were simulated to evaluate the algorithms. In literature for performance evaluation, the memory, time and energy consumption of algorithms are often considered for investigation.…”
Section: B Chaos-based Solutionsmentioning
confidence: 99%
“…The AES algorithm has been used for various wireless sensor network standards such as Zig Bee, Wireless HART and ISA100.11a. Both algorithms are evaluated on TelosB motes and it was demonstrated that the chaos-based algorithm is much faster than the AES-based algorithm with the same cryptography quality [25].…”
Section: Literature Surveymentioning
confidence: 99%
“…They have pseudo-random behavior for nonauthorized parties [Akhshani et al, 2012;El Assad et al, 2014;Kassem et al, 2014;Chiaraluce et al, 2002;Chen et al, 2004;Behnia et al, 2008;Wang et al, 2013;Chang, 2009]. Experimental results show that the chaos-based encryption algorithm can overcome security issues in efficient and adaptive ways compared to the classical encryption ones (such as DES and AES) [Abd El-Latif et al, 2012;Furht & Socek, 2003;Li et al, 2006;Bhargava et al, 2004;Mansour et al, 2012;Bhatnagar & Jonathan Wu, 2012].…”
Section: Introductionmentioning
confidence: 99%